DAKWAH PEKA KULTUR ALA AIPON ASSO: POTRET KEBERISLAMAN PEGUNUNGAN TENGAH PAPUA - Abu Muslim (Harmoni, 2014)
This is a biographical study of Islamic religious leaders. It utilizes a descriptive qualitative approach. This paper reviews religious patterns in Papua by focusing on the characteristics and role of religious leaders in society. Specifically, this study focuses on the biography of religious figure and Islamic fighter: Aipon Asso. He was a very industrious Chieftain in terms of spreading Islam in Papua, specifically in the village of Walesi, located in Jayawijaya regency. Although he did not have many educational qualifications, he was a key figure in the fight against the OPM. His religion was central to his fight. Through his political activities, Aipon Asso became a role model for citizens. As a Muslim, he became a patron and example for the people to embrace Islam. In short, the pattern of islamization in this case was top down. Simply put, people’s religious belief in Walesi was strongly influenced by the decisions of their leaders in selecting and struggling for his religious beliefs.